Breast feeding practice among the rural women in selected villages of Dumuria upazilla, Khulna - Zahan, Refat; Ferdaus, Farhana; Rahman, Md Abdur; Chowdhury, Shahin; Zahan, Effat; Islam, Md Ehsanul; Mamun, Md Shamsul Huda (Mediscope, 2020)
The study attempted to describe the pattern of breast feeding practice among the rural women of Bangladesh with last child below 5 years of age living in the villages of Dumuria Upazilla. Due to small size of study group limited analysis were possible yet important variables such as the level of maternal education, age of starting complementary food, food used during weaning period, maternal knowledge of importance of colostrum and feeding of colostrum to the infant were considered. One of the important variables of the study was the level of the education of the respondents. As per the study, the majority (41.06%) of the respondents passed secondary level. Maximum 90.0% mothers gave breast milk, 4.4% gave honey, 4.4% gave others and minimum 1.2% gave mixed food just after delivery. Majority 46% started breast feeding after 4 hours, 44.8% had within 1 hour, 6.8% after 1st hours, 2.4% after 3 hours of delivery. Maximum 89.2% of the respondent fed exclusive breast feeding up to 1-2 months, 9.6% fed up to 3-4 months, and 1.2% fed up to 5-6 months. Maximum 48.4% fed breast milk for 3-4 months. Maximum 88.8% started complementary food within 6 months, 11.2% after 6 months. Mediscope Vol. 7, No. 1: Jan 2020, Page 25-30